Metal–organic framework-derived Co9S8 embedded in N, O and S-tridoped carbon nanomaterials as an efficient oxygen bifunctional electrocatalyst. Issue 13 (14th March 2019) - Zhao, Jin-Yan; Wang, Rui; Wang, Shan; Lv, Ya-Ru; Xu, Hong; Zang, Shuang-Quan
Abstract : Designing a tailor-made MOF to prepare Co9 S8 embedded in N, O and S-tridoped carbon nanomaterials, which has a highly efficient electrocatalytic oxygen reaction activity. Abstract : Designing tailor-made metal–organic frameworks (MOFs) to synthesize target nanomaterials with extraordinary electrochemical oxygen catalytic activity is highly desirable. Here, we rationally designed a 2DCo-MOF [Co(BDC)2 (SPDP)2 (DMF)(H2 O)] (H2 BDC = 1, 4-benzenedicarboxylic acid, SPDP = 4, 4′-(sulfonylbis(4, 1-phenylene))dipyridine, DMF = N, N -dimethylformamide) as a single-source precursor through direct carbonization to afford an N, O and S-tridoped carbon matrix encapsulated with Co9 S8 nanocomposites (Co9 S8 @TDC ). By virtue of the intrinsic activity of Co9 S8 nanoparticles (NPs) as well as the heteroatom-doped carbon shell, Co9 S8 @TDC possessed excellent electrocatalytic activities for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) in alkaline solutions. In particular, Co9 S8 @TDC -900 displayed an overpotential of 330 mV ( vs. RHE) at current density of 10 mA cm −2 for OER and a half-wave potential of 0.78 V ( vs. RHE) for ORR with the limiting current density of 5.45 mA cm −2, rivalling the performances of RuO2 and Pt/C. As the proof of concept, Co9 S8 @TDC -900 was employed as a bifunctional oxygen catalyst for a rechargeable Zn–air battery, exhibiting a considerable open-circuit voltage (1.50 V) and impressive long-term charge/discharge stability (45 h at 5 mA cm −2 ). The straightforward strategy provides a facile method for the further exploration of non-noble metal electrochemical oxygen reaction catalysts.